2016
DOI: 10.5455/msm.2016.28.361-365
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Perceived Social Support on the Levels of Anxiety and Depression of Hemodialysis Patients

Abstract: Purpose:of this study was to explore the effect of social support on the levels of anxiety and depression of hemodialysis patients.Material and Methods:258 patients undergoing hemodialysis were enrolled. A questionnaire developed for the purpose of the study was used to collect data through the interview process. Apart from socio-demographic, clinical and other characteristics, the questionnaire also included the Multidimensional Scale of Perceived Social Support (MSPSS) to assess social support from significa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
30
2
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(39 citation statements)
references
References 27 publications
6
30
2
1
Order By: Relevance
“…Similarly, perceived social support in patients with chronic illness was a significant predictor of both depression and anxiety. 15,16 Chivukula, Swain, Rana and Hariharan 29 reported a negative impact of perceived social support on both anxiety and depression in cardiac patients. In another study, a negative relationship was found between depression and anxiety with perceived social support in patients with multiple sclerosis.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Similarly, perceived social support in patients with chronic illness was a significant predictor of both depression and anxiety. 15,16 Chivukula, Swain, Rana and Hariharan 29 reported a negative impact of perceived social support on both anxiety and depression in cardiac patients. In another study, a negative relationship was found between depression and anxiety with perceived social support in patients with multiple sclerosis.…”
Section: Discussionmentioning
confidence: 99%
“…• The Patients Information Form includes 24 questions about patients' sociodemographic characteristics, health-related issues, and disease characteristics, besides hospitaliZation-related matters. 13,[15][16][17] • HADS was developed in 1983 by Zigmond and Snaith. 18 It is a brief questionnaire that was originally designed to detect emotional disturbances in nonpsychiatric patients treated in hospital clinics.…”
Section: Data Collectionmentioning
confidence: 99%
See 1 more Smart Citation
“…The original version was constructed by Zimet et al (1988) and has been translated into other languages (Aloba, Opakunle, & Ogunrinu, 2019). The Greek version of MSPSS has good internal validity (Cronbach's α = .80) (Theofilou, Zyga, Tzitzikos, Malindretos, & Kotrotsiou, 2013) and has been used in elderly and haemodialysis patients (Lilympaki et al, 2016).…”
Section: Methodsmentioning
confidence: 99%
“…Depression may induce immune deficiency, loss of appetite, and malnutrition, rendering patients unable to cope with their prescribed therapy; depression can also provoke suicide, thus indirectly raising the mortality rate [10]. Gender, age, and comorbidity have been recognized as critical factors leading to depression [11]; lack of social support and a lengthy treatment regimen may also result in depression [12,13].…”
Section: Introductionmentioning
confidence: 99%